ANALISIS KANDUNGAN UNSUR HARA LIMBAH CAIR TEH HIJAU SEBAGAI BAHAN PUPUK ORGANIK PADA BIBIT TEH - Retno Muningsih; Gunawan Ciptadi (Universitas Wahid Hasyim, 2018)
Tea shoots processing intended to alter the chemical composition of fresh tea shoots, so bring the desired properties. Freshly plucked tea leaves containing water 75% of the weight of the leaves. The water contained in the leaves removed through the process of withering and drying in the processing of green tea. Green tea liquid waste obtained from the milling process and not used optimally, it needs a touch technology that can turn liquid waste into useful liquid organic fertilizer. The use of an activator / starter (micro-organisms) in green tea liquid waste is an alternative technology to improve the health and fertility of the soil and plants. The purpose of this study to determine the benefits of using liquid waste of green tea on the growth of tea seeds. Results of analysis of the utilization liquid waste of green tea with the addition of starter (EM-4) has not shown any real effect on the percentage of seedling growth and seedling growth (plant height, number of leaves and greenery). Keywords: liquid waste, green tea, organic matter.